APPLICATION OF JET AERATION FOR INCREASE OF WATER PURIFICATION EFFICIENCY IN THE SYSTEM OF WATER RECYCLING OF FOUNDRY CASTHOUSE - Ju. P. Ledjan; V. V. Selivonchik; M. K. Shcherbakova (Литьë и металлургия)
Construction of  high-efficient jet, allowing to fotm stream of  ring cross-section, providing sharp decrease of power inputs f o r  purification and decrease of  water flow, is developed.